(untitled) (International Journal of Engineering and Computer Science, 2018)
In the field of signal processing and communication, digital filter plays pivotal role. Digital FIR filter designed by different window techniques perform better for reducing noise from signal. In this paper, we design high-pass filter by using various window methods such as Hanning, Hamming, Blackman, Kaiser .This paper also provides comparative study of highpass filters using above window. It has been seen that Kaiser window is better with respect to Hanning, Hamming, Blackman window.